2016
DOI: 10.1055/s-0042-108733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Hot-Water Extract of Allium hookeri Roots on Bone Formation in Human Osteoblast-Like MG-63 Cells In Vitro and in Rats In Vivo

Abstract: is a wild herb found mainly in the Himalayas, growing at altitudes of 1400-4200 m. is widely consumed as a vegetable and herbal medicine in Asia, but its effects on bone health have not been reported previously. This study investigated the effects of a hot-water extract of roots on bone formation. The hot-water extract significantly increased the proliferation of human osteoblast-like MG-63 cells and the stimulatory effects on osteoblast differentiation were noticeably greater for the hot-water extract than fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Although various biological activities of AH root and leaf have been reported, the underlying mechanisms of AH remain unclear. So far, AH root and leaf showed anti-oxidant [ 14 – 16 ], anti-inflammatory [ 17 ], anti-microbial [ 18 ], improvement of bone health [ 19 ], anti-obesity [ 20 ] and anti-diabetic effects [ 21 – 23 ]. Our previous study reported that water extract of AH leaf or root revealed anti-diabetic effects in the type 2 diabetic db/db mice and in the pancreatic β-cell of streptozotocin (STZ)-induced diabetic rats [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although various biological activities of AH root and leaf have been reported, the underlying mechanisms of AH remain unclear. So far, AH root and leaf showed anti-oxidant [ 14 – 16 ], anti-inflammatory [ 17 ], anti-microbial [ 18 ], improvement of bone health [ 19 ], anti-obesity [ 20 ] and anti-diabetic effects [ 21 – 23 ]. Our previous study reported that water extract of AH leaf or root revealed anti-diabetic effects in the type 2 diabetic db/db mice and in the pancreatic β-cell of streptozotocin (STZ)-induced diabetic rats [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sulforaphane has been shown to epigenetically stimulate osteoblast activity and reduce osteoclast bone resorption [46]. Park et al [47] have also shown the alliin-containing vegetable, allium hookeri, to have in vitro and in vivo anabolic effects on bone formation. Allium hookeri is a widely consumed allium vegetable in Southeast Asia and is a rich source of alliin, an organosulfur compound that is also found abundantly in other allium vegetables such as garlic.…”
Section: Discussionmentioning
confidence: 99%
“…Allium hookeri has been consumed as medicinal food and contains a lot of rutin as an active ingredient. It is known to various biological properties such as antioxidant, antiobesity, antimicrobial, anti-inflammatory, and antiallergic effects [7][8][9][10][11][12]. Rutin, a quercetin-3-rhamnosylglucoside, has anti-inflammatory, antitumor, antiallergic, and vasoactive properties [13,14].…”
Section: Introductionmentioning
confidence: 99%